2018
DOI: 10.16986/huje.2018045432
|View full text |Cite
|
Sign up to set email alerts
|

%c4%b0lkokul%20ve%20Ortaokul%20%c3%96%c4%9frencileri%20i%c3%a7in%20%c3%96nerilen%20100%20Temel%20Eserde%20Karakter%20G%c3%bc%c3%a7lerinin%20%c4%b0ncelenmesi

Abstract: Bireyin duygu, düşünce ve davranışlarıyla ortaya koyduğu pozitif özellikler olarak tanımlanan karakter güçleri psikolojik sağlığa ve genel iyilik haline olan katkısı sebebiyle hem eğitimciler hem de psikoloji ve eğitim alanındaki uygulayıcılar için önemli bir çalışma alanı oluşturmaktadır. Bu çalışma ile MEB tarafından 2005 yılında ilkokul ve ortaokul öğrencileri için tavsiye edilen 100 Temel Eser listesinde yer alan kitapların karakter güçleri açısından incelenmesi amaçlanmıştır. Betimsel modele dayalı nitel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…For this reason, it can be said that LSCC aims to raise children who are temperate but not brave. Temperance, the most emphasized virtue in LSCC, appeared as the least emphasized virtue in the 100 fundamental literary works suggested for primary school students (Isik et al, 2019). In this sense, it is thought that LSCC and 100 fundamental literary works may balance each other in terms of the virtue of temperance.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…For this reason, it can be said that LSCC aims to raise children who are temperate but not brave. Temperance, the most emphasized virtue in LSCC, appeared as the least emphasized virtue in the 100 fundamental literary works suggested for primary school students (Isik et al, 2019). In this sense, it is thought that LSCC and 100 fundamental literary works may balance each other in terms of the virtue of temperance.…”
Section: Resultsmentioning
confidence: 96%
“…In addition to this, there is no study on whether these curriculums implicitly contain character strengths. In the Turkish literature, the only document examined in terms of character strengths is the 100 fundamental literary works recommended for primary and secondary school students (Isik, Kilic, Uzbe Atalay, Terzi Ilhan, & Kaynak, 2019). Since it is uncertain whether the 100 fundamental literary works will be read by all children, it is thought that examining the curriculums delivered to all children in terms of character strengths may contribute to the literature.…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of literature revealed a number of studies analysing other works in terms of character strengths. These studies, however, examine the works tailored towards preschool, primary and secondary school students (Aktu, 2023;Çetiner-Akalın & Murat, 2024;Işık et al, 2019). There is no such limitation in the current study.…”
Section: Discussion Conclusion and Suggestionsmentioning
confidence: 94%
“…On that basis, one might hold the view that understanding character strengths is becoming increasingly important. A review of related literature revealed that there are several studies employing this lens: In a study conducted by Işık et al (2019), character strengths were examined in 100 fundamental works that are recommended for primary and secondary school students in Türkiye by the Ministry of National Education (MEB). As the findings of the study reveal, the most emphasised character strength turns out to be loving while the least emphasised character strength is forgiveness.…”
Section: P Topuz Aslan Püsküllü Ve Argamentioning
confidence: 99%